2021
DOI: 10.12688/f1000research.27915.3
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of pyocyanin production by subinhibitory concentration of royal jelly in Pseudomonas aeruginosa

Abstract: Background: Pseudomonas aeruginosa, a multidrug-resistant Gram-negative bacterium, produces pyocyanin, a virulence factor associated with antibiotic tolerance. High concentrations of royal jelly have an antibacterial effect, which may potentially overcome antibacterial resistance. However, in some cases, antibiotic tolerance can occur due to prolonged stress of low-dose antibacterial agents. This study aimed to investigate the effect of subinhibitory concentrations of royal jelly on bacterial growth, pyocyanin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Other authors also described the low efficacity of royal jelly against P. aeruginosa. Amly et al (2021) showed that the pyoceanic pigment was eliminated by using a concentration of 25% of royal jelly [80]. In contrast, [81] showed that the MIC values for P. aeruginosa were higher, respectively, 60-100% (w/w), but similar to those against E. coli.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…Other authors also described the low efficacity of royal jelly against P. aeruginosa. Amly et al (2021) showed that the pyoceanic pigment was eliminated by using a concentration of 25% of royal jelly [80]. In contrast, [81] showed that the MIC values for P. aeruginosa were higher, respectively, 60-100% (w/w), but similar to those against E. coli.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…Amly et al (2021) [97] investigated the antibacterial activity of RJ against P. aeruginosa. The authors highlighted the potential of RJ to combat the resistance of this pathogen to antibiotics.…”
Section: Rj Against P Aeruginosamentioning
confidence: 99%
“…This represents a secondary metabolism product-specifically, a cytotoxic natural pigment. Pyocyanin is used in order to determine the pathogenicity of this microorganism [97]. However, pyocyanin has garnered great interest from numerous industries, medicine and agriculture as a colorant agent [98].…”
Section: Rj Against P Aeruginosamentioning
confidence: 99%